A mixed methods examination of emotional expression and its impact on emotion regulation effectiveness in borderline personality disorder. (June 2022) - Varma, Sonya; Traynor, Jenna; Fitzpatrick, Skye
Abstract: Background and objectives: Emotional expression (i.e., identifying and labeling emotion using specific words), is theorized to reduce negative emotion and facilitate emotion regulation. However, it remains unclear how individuals with borderline personality disorder express emotion, and whether this influences their emotion regulation. This study examined whether: 1) emotional expression in borderline personality disorder differed from healthy controls based on word valence, emotionality, and vocabulary; and 2) whether such characteristics predict emotion regulation effectiveness across self-reported and physiological emotion domains differentially across these groups. Methods: Individuals with borderline personality disorder (n = 29) and age and sex-matched healthy controls (n = 30) listened to an evocative story, expressed emotion, and regulated emotion by applying Mindfulness or Cognitive Reappraisal. Emotion regulation was measured by changes in self-report, parasympathetic, and sympathetic emotion, while implementing the emotion regulation strategies. The words used to express emotion were coded based on valence, emotionality, and depth of vocabulary. Results: Generalized estimating equations revealed no differences between groups in valence, emotionality, and vocabulary. Additionally, using a larger emotional vocabulary predicted more effective sympathetic emotion regulation, and using more negatively valenced words predicted more effective parasympathetic emotion regulation across groups. Limitations: Among other things, this study is limited by its predominantly female sample, and that it does not determine whether valence, emotionality, or vocabulary independently predict emotional expression effectiveness. Conclusions: Emotional expression may not be deficient in borderline personality disorder across the indices studied. Using more negative words and broadening vocabulary while expressing emotion may offer emotion regulation benefits. Highlights: Emotional expression may not be deficient in borderline personality disorder. Using a broader vocabulary to express emotion improves emotion regulation. Using more negative words to express emotion improves emotion regulation.